Majlis Makan Malam PKMA, 20 February 2016 - Universiti Malaysia Sarawak, Centre for Academic Information Services (Centre for Academic Information Services (CAIS), 2016)
CAIS Annual Dinner has been held at Waterfront Hotel on the 20th February 2016.